Estratigrafia, geoquímica isotópica (C-O) e paleogeografia da Formação Lagoa do Jacaré (Ediacarano-Cambriano), Grupo Bambuí, Minas Gerais - Márcio Vinicius Santana Dantas (2022)
The Lagoa do Jacaré Formation occurs in the middle section of the Bambuí Group, composed by dark gray carbonates with high values of ẟ¹³C, being part of the Middle Bambuí Excursion (MIBE), deposited during the Ediacaran-Cambrian boundary. Sedimentary facies and ẟ13C e ẟ18O isotopic data were analyzed in four outcrops in the Minas Gerais state, coupled with conventional petrographic analysis and SEM with EDS, besides the interpretation of a seismic line and three well logs in the surroundings of the Januária High. Eight sedimentary facies were recognized and and grouped into five facies associations that corresponds to a homoclinal carbonate ramp model with mixed carbonate-siliciclastic sedimentation. They represent peritidal environments (FA1), offshore fine siliciclastics (FA2), mid-ramp tempestites in the offshore-shoreface transition (FA3), offshore fine carbonate on outter ramp (FA4), and ooidal carbonate banks shoals in the inner ramp (FA5). It was possible to recognize grainstones and wackestones with pyritized intraclasts, micro-oncoids and ooids, as well as fine terrigenous material (silt fraction) (quartz, feldspar, muscovite, biotite, apatite) with some autigenic/diagenetic minerals (pyrite, fluorite, titanite, rutile). Towards the south, in the region of Paraopeba-Curvelo, the section studied has up to 100 m of thicknesses, with mean isotopic value of +12,60‰ to ẟ13C. To the north, between Montes Claros and Ubaí cities, the thickness increases to 300 m, as identified in the well log, although with the lowest mean value of ẟ¹³C (+9.53‰). These high values are believed to result from high rates of organic matter burial and/or low water circulation in a stratified sea. These difference in mean values may be related to different stratigraphic intervals of the Lagoa do Jacaré Formation: the lower in the south and the upper in the north. To the south, a 100 m-thick homoclinal ramp predominates, deposited in the forebulge, foredeep and wedge-top sectors of a foreland type basin. Between the Januária High (west) and the Araçuaí orogeny (east), a large carbonate ramp with N-S direction was developed in the back-bulge sector, according to the paleocurrent measurements (directions main W-E). The lower mean values of ẟ¹³C in this upper part of the section may be related to a possible reconnection of the previously isolated oceans of the Lagoa do Jacaré Formation with global oceans or a gradual decreasing of organic productivity, in the final stages of deposition of this unit in the Cambrian period.